Disaster Readiness and Risk Reduction Students' Academic Achievement in a Web-Based Learning Platform - Enero, Leah Mae (Archīum Ateneo, 2019)
Second Life (SL) is an online virtual world with pedagogical applications such as digital storytelling, role-playing, and community engagement. As a web-based learning platform, Second Life has already gained the attention of educators around the globe, however, this has not been explored yet in the local educational setting. In an environment where an efficient and effective transfer of learning is becoming a challenge amidst technological advancements, this studyproposes the use of Second Life as a web-based learning platform in delivering classroom instruction for senior high school students aging 16-17 years old. This study aims to identify the effect of using Second Life in the academic achievement of the learners. The respondents were from a city-funded local university involving two sections comprised of 30 students each with similar cognitive ability, where one of the groups used the traditional approach and the other used Second Life as a learning platform. In this study, the computed mean value for the non-SL group was 20.10 and 29.93 for the SL group. Based on the level of proficiency, this showed a significantly higher post-academic achievement with 77% of the SL group as compared to the 0% of the non-SL group in terms of the frequency of students at the outstanding level. The delivery of classroom instruction, which may be challenging but incorporating technology as a part of the 21st century learning, will be an advantage to both the teacher and the students.